Effect of sintering on the physical and mechanical properties of Co-Cr-Mo (F-75)/HAP composites - Nur Maizatul Shima, Adzali, Dr. (Universiti Kebangsaan Malaysia, 2014)
Link to publisher's homepage at http://www.ukm.my/